Uma proposta de roteiro turístico como ferramenta ao desenvolvimento sustentável para o município de Dr. Ulysses-PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Tourism can play a fundamental role in socioeconomic development, especially in small municipalities, established in rural and traditional areas, by promoting local culture and geodiversity. Its practice, however, can generate several impacts, both positive and negative, depending on the control and planning of its implementation. The landscape of the study region – Vale do Ribeira –, encompassing its geodiversity, often triggers tourist activity, as in the case of adventure tourism, cultural heritage and also karst tourism, given the presence of 26 caves in the municipality by Dr. Ulysses. This includes the largest cavity in Paraná, Gruta Dá a Volta, 2,675 meters long. Identifying, characterizing and publicizing existing tourism potential is essential for adequate management and effective administration. This dissertation proposes a “Tourist itinerary as a tool for sustainable development for the municipality of Dr. Ulysses”, aiming to explore landscape elements with potential for tourism and the development of the local community. The research involves analyzing the relationship between tourism and sustainable development, using classic theories and current research, to identify the tourist potential of Dr. Ulysses. Focusing on this municipality, located in the Vale do Ribeira region and in the northern portion of the metropolitan region of Curitiba, one of the richest and most developed in Brazil, we seek to understand the dichotomy between the municipality's low HDI and its scenic potential for the tourist use, and how the karst landscape intertwines with cultural aspects, such as the traditional production of yerba mate and ponkan farming, creating a unique identity – that of “Countryside Tourism”. The methodology used included fieldwork and production of maps through GIS, which allowed a comprehensive analysis of the geological and cultural characteristics of Dr. Ulysses. The results, based on the extensive literature review, the questionnaires applied and the fieldwork, reveal the importance of tourism in promoting sustainable local development and highlight the need to preserve and consciously promote the region's geoheritage.
Keywords: Potencial turístico; cavernas e geodiversidade; desenvolvimento local; roteiro turístico; Touristic potential; caves and geodiversity; local development; tourist itinerary; CNPQ::CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS